A Fuzzy Set-Based Model for Educational Serious Games with 360-Degree Videos - Zildomar Carlos Felix; Liliane S. Machado; Rodrigo Pinheiro de Toledo Vianna; Ronei Marcos de Moraes (International Journal of Computer Games Technology)
Currently, the use of 360° videos combined with virtual reality (VR) techniques in the educational context has been considered a promising field of research. However, there is still a shortage not only of educational serious games (ESG) that implement such resources but also of models that can enhance the player’s experience and evaluate their performance. This work presents a decision model for SGE with 360° videos. The model was developed from artificial intelligence (AI) techniques with the aim of enhancing the player’s learning using immersion mechanisms and pedagogical reinforcement strategies based on the player’s experience and performance evaluation. The model was integrated into the SG The Mystery of Pandora to evaluate its efficiency. The game was evaluated with a sample of 52 participants aged between 13 and 63 (M=33.55, SD=12.14). The results showed adjustments made by the model in the final performance of the players based on their exploration in the 360° videos. Such adjustments allowed identifying players with learning difficulties and recommending pedagogical reinforcement to enhance learning. It was also possible to verify that players would win the game without the minimum knowledge expected about the subject if the decision model was not used.